Trade union organizations and the modernization of labor relations in Chile - Acuña A., Eduardo (Estudios de Administración, 1997)
The present paper inquires into the capacity of Chilean unions to participate as collaborators in the modernization of labor relations at the level of firms. The content postulates that, if unions are to render an effective participation, previous organizational changes are required. The article extends into a deep analysis of the nature of such changes.